2017
DOI: 10.1149/07801.1559ecst
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Oxidation on Dual Atmosphere Effect on AISI 441 Interconnects for Solid Oxide Fuel Cell Applications

Abstract: In previous studies an extreme dual atmosphere effect on the airfacing side of AISI 441 at 600°C was observed. However indications showed that pre-oxidation of the material might have a beneficial effect on the corrosion resistance in dual atmosphere. To examine this further we pre-oxidized AISI 441 samples for 0 min, 11 min, 45 min, 180 min and 280 min and subsequently exposed these at 600 °C for 500 h under dual atmosphere conditions. Photographs of the air-facing sides were taken throughout exposure to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…What is, however, agreed upon, by different researchers in the field, is that hydrogen is the culprit (13)(14)(15). This is also supported by our recent studies on the effect that pre-oxidation has on the dual atmosphere effect (16,17). Here we showed that the pre-oxidation layer on the fuelfacing side is more important as a useful mitigation strategy against the dual atmosphere effect than the pre-oxidation layer on the air-facing side.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…What is, however, agreed upon, by different researchers in the field, is that hydrogen is the culprit (13)(14)(15). This is also supported by our recent studies on the effect that pre-oxidation has on the dual atmosphere effect (16,17). Here we showed that the pre-oxidation layer on the fuelfacing side is more important as a useful mitigation strategy against the dual atmosphere effect than the pre-oxidation layer on the air-facing side.…”
Section: Introductionsupporting
confidence: 82%
“…All coupons were ultrasonically cleaned in ethanol and acetone before pre-oxidizing them for 20 min at 800 °C in an air flow rate of 280 sml min -1 and 3 % water vapor. The pre-oxidation length was chosen because previous studies have shown that shorter pre-oxidation times result in accelerated corrosion in dual atmosphere (16,17). The other pre-oxidation parameters, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…(10,11). Promoting the formation of a chromia scale at the fuel side through pre-oxidation treatments in air effectively delays the onset of breakaway corrosion (1,2). These findings were in line with hydrogen permeation measurements by Kurokawa et al who reported that hydrogen permeation is faster through the steel, rather than through the Cr2O3 scale (12,13).…”
Section: Introductionsupporting
confidence: 79%
“…Hence, in this study, the effect of humidity content in the fuel gas was investigated. This parameter might affect the oxidation behavior of the FSS on the fuel side(14) (chromia thickness, breakaway corrosion etc..) which in return affects the protectiveness of the airside as well (2).…”
Section: Introductionmentioning
confidence: 99%